Rank Size Rule Analysis on the Urban Population Distribution of Indonesia for the Year 2020 - Mohaqiq, Mohammad Sadiq (International Journal of Scientific Research and Management (IJSRM), 2024)
The rank-size rule which is known as Zipf``s law is an interesting research topic in the field of urban and regional studies. Conclusions are drawn based on the parameters that examine people and their economic activities in a particular city. this study aims to assess the unique urban development and population distribution of Indonesia by taking into account the complex socioeconomic system and geographically different archipelago. This study uses demographical data from various cities in Indonesia to understand the hierarchal pattern of population distribution in urban areas. Furthermore, Indonesia is an interesting case study regarding urban economics since it has a vast geographical area and contains different cultures and economic activities. The main objective of this research is to understand the population distribution and to evaluate the accuracy of the rank-size rule model in this country. This research also aimed to identify the main factors that deviate the population distribution from the rank-size rule distribution. It is particularly important to develop practical policies on the urban development issues. The minor variations of population distribution in Indonesia from the rank-size rule model are a good tool for decision-makers to allocate resources, develop infrastructure, and contribute to sustainable urban expansion. In addition, this study is significant for understanding how the urban centers developed in Indonesia and how they interact with broader socio-economic perspectives which is essential for further urban development and wise decision-making.